2019
DOI: 10.1097/md.0000000000018196
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, risk factors, and prognostic value of anxiety and depression in refractory or relapsed acute myeloid leukemia patients of North China

Abstract: This study aimed at investigating the prevalence of anxiety and depression, and their risk factors as well as their correlation with prognosis in refractory or relapsed (R/R) acute myeloid leukemia (AML) patients.A total of 180 R/R AML patients were enrolled and their anxiety and depression were assessed by Hospital Anxiety and Depression Scale (HADS) before treatment. Besides, HADS was also evaluated in 180 de novo AML patients prior treatment and 180 healthy controls (HCs), respectively.Both the HADS-Anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It has been reported that patients with hematological cancers experience anxiety and depression [36,37]. Studies also suggest the same effects on patients with hematological relapse [38,39], which is not surprising given that they face yet another life-threatening situation. Fear of recurrence has been reported as a major concern for this patient population after treatment completion [36,40,41] and would be expected to lead to anxiety, as would relapse when it is diagnosed.…”
Section: Results In a Clinical Contextmentioning
confidence: 87%
“…It has been reported that patients with hematological cancers experience anxiety and depression [36,37]. Studies also suggest the same effects on patients with hematological relapse [38,39], which is not surprising given that they face yet another life-threatening situation. Fear of recurrence has been reported as a major concern for this patient population after treatment completion [36,40,41] and would be expected to lead to anxiety, as would relapse when it is diagnosed.…”
Section: Results In a Clinical Contextmentioning
confidence: 87%
“…After enrollment, the anxiety and depression of participants were assessed using the Hospital Anxiety and Depression Scale (HADS). 19 , 20 , 21 After given description of scale filling by the investigator, participants were required to complete the HADS by themselves. Then, researchers assessed the anxiety and depression of participants using HADS.…”
Section: Methodsmentioning
confidence: 99%
“…During follow-up, anxiety, and depression of the patients were assessed using HADS at baseline (M0), month 3 (M3), month 6 (M6), month 9 (M9), month 12 (M12), month 15 (M15), month 18 (M18), month 21 (M21), month 24 (M24), month 27 (M27), month 30 (M30), month 33 (M33), and month 36 (M36). [15][16][17] The HADS has 14 items: 7 items were designed for anxiety measuring HADSanxiety (HADS-A) and other 7 items were designed for depression measuring HADS-depression (HADS-D). The total score of HADS-A was ranging from 0 to 21, and the total score ≥8 was defined as anxiety.…”
Section: Treatment Follow-up and Assessmentmentioning
confidence: 99%